Collaborative Governance To Increase The Absorption of Alumni of Job Training Participants Into Industrial World - Aris Rismawan, Deni; Sugiarto, Yanto; Hermawati, Sri; Susanti, Susi (Green Publisher Indonesia, 2024)
UPTD BLK Kuningan Regency is committed to improving professionalism and workforce competence in Kuningan Regency through the implementation of skills training, but besides this, UPTD BLK Kuningan Regency also plays a role in fostering alumni of job training participants, one of which is in the form of facilitating job security for alumni participating in job training. Starting from this, collaborative governance is an absolute thing that must be done by UPTD BLK Kuningan Regency. The type of research used is descriptive research with a qualitative approach. The focus of the research uses the theory of the collaborative governance process according to Ansell and Gash (2007) which consists of Face to Face Dialogue, Trust Building, Commitment to The Process, Shared Understanding and Intermediate Outcome. The results of the study show that 5 indicators of the collaborative governance process proposed by Ansell and Gash (2007:228) have been carried out by each stakeholder.